New QTLs for lint percentage and boll weight mined in introgression lines from two feral landraces into Gossypium hirsutum acc TM‐1. Issue 1 (4th January 2016) - Zhang, Shuwen; Feng, Liuchun; Xing, Luting; Yang, Biao; Gao, Xiang; Zhu, Xiefei; Zhang, Tianzhen; Zhou, Baoliang
Abstract: Overuse of a small number of Upland cotton cultivars has narrowed cotton's genetic base, leading to major difficulties in developing cotton cultivars with diverse genetic backgrounds that are able to adapt to adverse conditions. To effectively broaden the genetic base, chromosome introgression lines (ILs) were developed, where TM‐1, the genetic standard of Upland cotton, was used as the common recipient and its two feral landraces, TX‐256 and TX‐1046, were used as the donors. A total of 115 ILs, with an average segment length of 11.15 cM, were first developed via intraspecific hybridization by marker‐assisted selection (MAS) in BC3 F2 generations, spanning 3887.75 cM of the cotton genome. Association analysis showed that 63 markers were found to be associated with boll weight (BW), lint percentage (LP) and seed index. The percent of phenotypic variance explained by 148 QTLs detected was 4.12% on average. Eleven and five new QTLs for BW and LP (one stable QTL identified for LP in all environments) were detected, respectively, which can be used for efficiently pyramiding favourable alleles into one cultivar by MAS.